Bounded cohomology, Higgs bundles, and Milnor-Wood inequalities - Hartnick, Tobias; Ott, Andreas (Arxiv, 2020)
We explain how the generalized Milnor-Wood inequality for reductive representations of a cocompact complex-hyperbolic lattice into a Hermitian Lie group translates, under the non-abelian Hodge correspondence, into various kinds of Milnor-Wood inequalities for Higgs bundles. This clarifies the relation between the representation theoretic generalized Milnor-Wood inequality and the various different versions of Milnor-Wood inequalities for Higgs bundles that are known in the literature.
Online veröffentlicht am 22. Mai 2011, Version 2 am 28. Sepember 2018, Version 3 am 14. April 2020
Gesehen am 10.01.2024